Sexual dimorphism in a freshwater atyid shrimp (Decapoda: Caridea) with direct development: a geometric morphometrics approach - Sganga, Daniela Eliana; Piana, Lucas Raul Fernandez; Greco, Laura Susana López (Zootaxa, 2016)
Neocaridina davidi is a caridean shrimp that has gained popularity in recent years as an ornamental species. Using geometric morphometrics, we investigated sexual dimorphism in carapace and second abdominal segment shape of N. davidi. Adult females displayed a more elongated carapace and a longer rostrum than males. However, male carapace shape was similar to that of juvenile females. The second abdominal pleura was more elongated and wider in adult females than in males. Significant differences were found in centroid size for the carapace and the second abdominal segment between sexes, which is consistent with sexual size dimorphism. These results support the hypothesis of a “pure search” mating system in N. davidi, where small males search actively for receptive females, and after insemination they continue searching.